2011
DOI: 10.1080/0886571x.2011.569427
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Emotional Regulation for Youths in Residential Care: Phases of Change

Abstract: Youths in residential care have likely experienced trauma as they have had atypical and disruptive events occur in their lives that has contributed to their out-of-home placement. For people who have been traumatized, the regulation of emotions is an important feature of their recovery. This article presents a model that traces phases from emotional dysregulation to increased regulation. Specific clinical descriptions of the youths are provided for each of the proposed phases. Youth care staff preferred treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Our findings reinforce that phased approaches to youth residential mental health support can support staff to predict challenges and understand what might be happening for someone and why (Cimmarusti, 2011; Downey et al, 2015). They attune staff to individual and community needs, not time‐based expectations of ‘progress’.…”
Section: Discussionsupporting
confidence: 76%
“…Our findings reinforce that phased approaches to youth residential mental health support can support staff to predict challenges and understand what might be happening for someone and why (Cimmarusti, 2011; Downey et al, 2015). They attune staff to individual and community needs, not time‐based expectations of ‘progress’.…”
Section: Discussionsupporting
confidence: 76%
“…Further influencing an adolescent's ability to accurately read a situation is their mental model, how they view the world around them. Increasing awareness of mental models (how adolescents view their world) may assist in improving the abilities of adolescents to reason, judge and act prosocially in a socio-moral context (Cimmarusti, 2011). As this research connotes, experiences are mediated by emotion (felt and anticipated).…”
Section: Moral Emotions In Adolescencementioning
confidence: 94%
“…All three stages help the adolescent in evaluating either positive or negative emotions experienced and taking appropriate action. Cimmarusti (2011) recommended focusing first on awareness of emotion, and then accurately labelling the emotion. This can be achieved by asking adolescents, 'What are you feeling?'…”
Section: Moral Emotions In Adolescencementioning
confidence: 99%
“…The ONS study (Meltzer et al, 2003) indicated that as many as 70% of adolescents in residential care homes in England had a mental health disorder and other studies have reported rates as high as 97% (McCann et al, 1996). Additionally, studies which examined the impact of childhood maltreatment, such as abuse and neglect, on mental health outcomes have indicated a wide range of emotional and psychological problems ranging from attachment difficulties (Schofield & Beek, 2005;Bentovim, 2006;Tanner & Turney, 2006;Fearon et al, 2010) and problems regulating emotions (Cimmarusti, 2011) to mental health disorders and suicidal ideation (Skowron & Reinemann, 2005).…”
Section: Mental Health Of Maltreated Youthmentioning
confidence: 99%